2021
DOI: 10.1155/2021/4091888
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Closure of Perimembranous and Intracristal Ventricular Septal Defects Using Amplatzer Duct Occluder II in Children

Abstract: Background. Transcatheter closure of aneurysmal perimembranous ventricular septal defect (pmVSD), pmVSD near the aortic valve, and intracristal VSD (icVSD) with symmetrical or asymmetrical ventricular septal defect occluders still presents significant challenges. We report our experience with transcatheter closure of pmVSD and icVSD using Amplatzer duct occluder II (ADO II) in children. Method. We retrospectively analyzed all children, who presented to our hospital consecutively between March 2014 and June 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
1
2
1
Order By: Relevance
“…Recently, Tang et al reported using ADO II to close small doubly committed subarterial VSDs (1.5–3.5 mm) ( 28 ). In their short-term study (1–45 months), only 1/24 developed new-onset mild AR, which was similar to our recent report (1/13) ( 28 , 29 ). Therefore, ADO II may be one of the options for small icVSD because its material is softer than other occluders, which may preclude sustained damage to the aortic valve.…”
Section: Discussionsupporting
confidence: 90%
“…Recently, Tang et al reported using ADO II to close small doubly committed subarterial VSDs (1.5–3.5 mm) ( 28 ). In their short-term study (1–45 months), only 1/24 developed new-onset mild AR, which was similar to our recent report (1/13) ( 28 , 29 ). Therefore, ADO II may be one of the options for small icVSD because its material is softer than other occluders, which may preclude sustained damage to the aortic valve.…”
Section: Discussionsupporting
confidence: 90%
“…Occluder type was considered to be different in the comparison of general characteristics. Adjusted multivariate analysis did not suggest that occluder-related factors were the possible risk factors for AR requiring unplanned surgery, surprisingly, while according to our understanding and experience from other studies occluder-related factors should be associated with the occurrence of AR [15, 25, 27, 28]. This may result from the small number in AR group in our study.…”
Section: Discussioncontrasting
confidence: 66%
“…A milestone and the top level of the nonbiodegradable occluder so far is the nanocoated occluder of the left atrial appendage with a modified surface to achieve appropriate cell responses, which has been pioneered and developed by the Ding team from the Orient 16 . The next‐generation occluder is expected to be biodegradable, because the permanent presence in the human body may probably cause various adverse reactions, like hemolysis, thrombosis, metal allergy, toxic reaction, valve damage, heart perforation, and even severe arrhythmia 17–24 . Furthermore, implantation of metal ASD or PFO occluders will obstruct the transseptal access to the left atrial.…”
Section: Introductionmentioning
confidence: 99%
“…16 The next-generation occluder is expected to be biodegradable, because the permanent presence in the human body may probably cause various adverse reactions, like hemolysis, thrombosis, metal allergy, toxic reaction, valve damage, heart perforation, and even severe arrhythmia. [17][18][19][20][21][22][23][24] Furthermore, implantation of metal ASD or PFO occluders will obstruct the transseptal access to the left atrial. It may impede the future transcatheter operation for acquired heart disease, such as mitral valvuloplasty, left atrial appendage occlusion, pulmonary vein angioplasty, and radiofrequency ablation for atrial arrhythmia.…”
mentioning
confidence: 99%